Characterization of sugar palm nanocellulose and its potential for reinforcement with starch-based composite - Rushdan, Ahmad Ilyas; Salit, Mohd Sapuan; Ishak, Mohamad Ridzwan; Zainudin, Edi Syams; Mahamud, Atikah (CRC Press, 2019)
Plant, wood and lignocellulosic fibres (sugar palm fibre, etc.) are naturally formed cellular hierarchical green-composite polymers, composed of aggregated semi-crystalline cellulose microfibrils cemented with amorphous matrices such as lignin, hemicellulose, waxes, extractive and other trace elements. Nanocellulose can be isolated from this naturally occurring polymer, due to the hierarchical structure of cellulose. Chemical or mechanical processes (or a combination of both) allow the extraction of more or fewer individual nanofibres. Longitudinal or horizontal cutting of the microfibres can be done either using multiple mechanical shearing forces or a strong acid hydrolysis process, which leads to the removal of the amorphous region. The remarkable characteristics of these bionanomaterials, such as abundant surface hydroxyl groups, large specific surface area, high aspect ratio, high crystallinity, high thermal resistance, good mechanical properties, and low density along with biocompatibility and biodegradability, make them perfect candidates to be reinforced with polymer nanocomposite (bio-plastic and petroleum-based plastic) for various potential applications, from food packaging material to military industry. The development of green nanocomposites can generate significant environmental improvements, addressing disposal of plastic waste and the reduction of the carbon footprint of commodities derived from petroleum-based polymer.